The Wurumana Institution in the Life of the Lio Ethnic Group - Samun, Samun; Lampe, Munsi; Muis, Safriadi (Borong Newinera Publisher, 2025)
This study explores the Wurumana institution within the Lio ethnic community of Maurole Village, East Nusa Tenggara, using a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and document analysis. The research identifies three main functions of Wurumana: (1) fulfilling bridewealth obligations (belis), facilitating collective resource mobilization for marriage payments; (2) reinforcing kinship solidarity, strengthening communal bonds; and (3) providing a conflict resolution mechanism through customary mediation. The ritual unfolds in nine stages, beginning with family summons and ending with the presentation of rice, garments, and Lio woven textiles. The persistence of Wurumana is explained by three factors: the moral principle of jaga waka (preserving familial dignity), the authority of the Eda (traditional leaders), and the tau tei duna mea ethic (the cultural imperative of contribution, enforced through social sanctions). This study highlights the enduring relevance of Wurumana in contemporary Lio society and contributes to understanding the social organization of the Lio ethnic group.